The HBCU advantage: reimagining social capital among students attending black colleges - Johnson, Jennifer M.; Jackson, Elizabeth (Frontiers in Education, 2024)
There is growing interest in exploring the ways Historically Black Colleges and Universities (HBCUs) mediate student outcomes. Situating an HBCU education within the conceptual landscape of social capital, we follow the tenets of critical discourse analysis (CDA) to explore the narratives of ten early and mid-career HBCU alumni of eight 4-year colleges and universities. This framing allows for a nuanced analysis of the ways in which an HBCU education provides its students the opportunity to curate social capital in an environment that affirms racial identity and promotes continued service to the Black community. Findings support the notion that as purveyors of social capital, HBCUs facilitate the transmission of knowledge through relationships and networks that strengthen community ties and leads to educational and professional gains. These findings inform our understanding of the experiences, policies, and practices that promote community building and the successful career transitions among Black college graduates.